Penerapan Konseling Karir Dengan Pendekatan Trait And Factor Dalam Pengambilan Keputusan Karir Siswa SMA - Wirdatun Nisya; Daharnis Daharnis; Nurfarhanah Nurfarhanah (Jurnal Ilmiah Wahana Pendidikan, 2023)
The application of counseling to make career decisions for students needs to be done carefully and use an appropriate approach. One counseling approach that is suitable for overcoming the problem of career selection is traits and factors. The method used in this research is library research. How to collect data with documentation and find written sources according to the traits and factors approach for career decision making. The results of this study are that the trait and factor counseling approach can influence and be used to make career decisions for high school students whether to continue their study program or in a field of work that is definitely in accordance with their potential talent interests.